2019
DOI: 10.1002/cncy.22205
|View full text |Cite
|
Sign up to set email alerts
|

Targeted deep sequencing of cell‐free DNA in serous body cavity fluids with malignant, suspicious, and benign cytology

Abstract: BACKGROUND: Liquid biopsy using cell-free DNA (cfDNA) presents new opportunities for solid tumor genotyping. While studies have demonstrated the utility of cfDNA from plasma, cfDNA from other body fluids remains underexplored. METHODS:We evaluated the molecular features and clinicopathologic correlates of cfDNA from serous body cavity fluids by performing hybrid capture-based next-generation sequencing (NGS) on cfDNA isolated from residual effusion supernatants. Twenty-one serous effusions from pleural (n = 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 65 publications
(81 reference statements)
3
26
0
Order By: Relevance
“…Although the cytology formalin fixed paraffin embedded (FFPE) cell block (CB) is commonly used for molecular testing, post-centrifugation cytology supernatant (CCS) has been shown to serve as a viable alternative. [5][6][7][8][9][10][11][12][13] Previous reports have suggested that CCS for NGS analysis may be associated with improved turnaround time (TAT) and cost savings. [6][7][8][9] In this study, we reviewed our implementation process to evaluate its performance and share our experience with the improved molecular cytopathology workflow using previously discarded CCS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the cytology formalin fixed paraffin embedded (FFPE) cell block (CB) is commonly used for molecular testing, post-centrifugation cytology supernatant (CCS) has been shown to serve as a viable alternative. [5][6][7][8][9][10][11][12][13] Previous reports have suggested that CCS for NGS analysis may be associated with improved turnaround time (TAT) and cost savings. [6][7][8][9] In this study, we reviewed our implementation process to evaluate its performance and share our experience with the improved molecular cytopathology workflow using previously discarded CCS.…”
Section: Introductionmentioning
confidence: 99%
“…Communication among clinical treatment teams, cytopathology, and molecular pathology laboratories is essential to ensure these limited samples are sufficient for both primary diagnosis and subsequent molecular testing. Although the cytology formalin fixed paraffin embedded (FFPE) cell block (CB) is commonly used for molecular testing, post‐centrifugation cytology supernatant (CCS) has been shown to serve as a viable alternative 5‐13 . Previous reports have suggested that CCS for NGS analysis may be associated with improved turnaround time (TAT) and cost savings 6‐9 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite good results in PF cell pellets, other studies suggest that NGS on body fluid supernatants possesses higher performance for detecting EGFR mutations in cfDNA compared to body fluid sedimentary tumor cells and plasma cfDNA specimens [ 49 ]. In addition, targeted hybrid capture deep sequencing for the analysis of 130 cancer-related genes confirmed the presence of mutations in 15 PF supernatants where median depth of target was >1000× [ 50 ]. High concordance was seen between PF and FFPE samples.…”
Section: Tumor-derived Products In the Pleural Fluidmentioning
confidence: 99%
“…More recently, tumor-derived cfDNA from other specimen types, including cerebrospinal fluid, urine, serous effusion fluid, and fine needle aspiration (FNA) supernatant has also been sequenced with favorable results (8)(9)(10)(11)(12)(13)(14)(15). Effusion fluid, in particular, is enriched in cfDNA species, making it a perfect medium for molecular testing (12,(16)(17)(18)(19)(20). A major advantage of using such specimens is that they are largely derived from patients with unresectable, advanced stage malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Their collection is minimally invasive, and their utilization can spare patients the discomfort and morbidity associated with more invasive procedures. Several studies have demonstrated that effusion specimens represent a robust source of genetic material for tumor profiling (12,16,17,21). However, several important pre-analytical variables in sequencing of effusionderived cfDNA testing remain unclear.…”
Section: Introductionmentioning
confidence: 99%